1975
DOI: 10.1083/jcb.64.2.461
|View full text |Cite
|
Sign up to set email alerts
|

Externally disposed plasma membrane proteins. II. Metabolic fate of iodinated polypeptides of mouse L cells.

Abstract: The fate of the L-cell plasma membrane proteins labeled by enzymatic iodination was studied. The disappearance of label from growing cells exhibits a biphasic behavior, with 5-20% lost rapidly (t~ ~ 2 h) and 80-90% lost relatively slowly (t~ ~ 25-33 h). The loss is temperature dependent and serum independent, and is accompanied by the appearance of 51% [l~5l]monoiodotyrosine (MIT) in the medium by 47 h. A variable amount (1-14%) of acid-insoluble label can be recovered in the medium over 47 h. Sodium dodecyl s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
1

Year Published

1976
1976
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(62 citation statements)
references
References 34 publications
8
53
1
Order By: Relevance
“…In the latter, it became possible to document the relatively slow turnover of most plasma membrane proteins in cultured cells. When Hubbard and Cohn coaxed L cells to phagocytose latex particles, they found that the phagocytic vacuole membrane contained a representative sample of plasma membrane polypeptides, and that phagocytosis was associated with a much more rapid turnover of these polypeptides (103). Werb made similar findings on the effect of phagocytosis on the turnover of the plasma membrane enzyme, 5'-nucleotidase (79).…”
Section: The Macrophage Plasma Membrane and Membrane Recyclingsupporting
confidence: 57%
“…In the latter, it became possible to document the relatively slow turnover of most plasma membrane proteins in cultured cells. When Hubbard and Cohn coaxed L cells to phagocytose latex particles, they found that the phagocytic vacuole membrane contained a representative sample of plasma membrane polypeptides, and that phagocytosis was associated with a much more rapid turnover of these polypeptides (103). Werb made similar findings on the effect of phagocytosis on the turnover of the plasma membrane enzyme, 5'-nucleotidase (79).…”
Section: The Macrophage Plasma Membrane and Membrane Recyclingsupporting
confidence: 57%
“…In particular, the pathway leading to the degradation of this pentameric ion channel remains largely elusive. Evidence for lysosomal degradation of CHRN comes from studies using iodinated protein flux 45,46 and from the effects of lysosomal inhibitors on CHRN levels in C2C12 muscle cells. 18,47 Given the recent discussions about the physiological roles of TRIM63 in muscle atrophy and the findings of its possible function in the turnover of the CHRN, we focused on this process in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…During endocytosis, the plasma membrane invaginates and encloses extracellular fluid (pinocytosis) or particles (phagocytosis) in plasma-membrane-derived vesicles. This process leads to an extensive internalization of plasma membrane varying between 1 and 20 times the total cell surface area per hr, depending on cell type and culture conditions (6)(7)(8)(9)(10)(11)(12). However, during endocytosis no reduction of the cell surface area is observed.…”
Section: Ammentioning
confidence: 99%